Der Prozess Jesu - aus römisch-rechtlicher Perspektive - Paulus, Christoph G. (Schriftenreihe der Juristischen Gesellschaft zu Berlin, 2016)
Although it is clear that the trial of Jesus has been extensively discussed and described before, new aspects are revealed by a strict focus on the written text from the perspective of legal history. The author follows this approach and comes to the inexorable conclusion that Jesus`s sentence was fully consistent with the terms of Roman penal and procedural law.